1995
DOI: 10.1007/bf00052771
|View full text |Cite
|
Sign up to set email alerts
|

Early body size and subsequent weight again as predictors of breast cancer incidence (Iowa, United States)

Abstract: We examined whether associations of adult weight gain with the risk of postmenopausal breast cancer vary by stature, waist-hip ratio (WHR), and early adult size in a cohort of 37,105 Iowa (United States) women. Both low body mass index (kg/m2) (BMI) at age 18 and high subsequent weight-gain were associated independently with increased risk of incident postmenopausal breast cancer. After stratifying on BMI at age 18, high weight gain was associated with increased risk irrespective of whether early BMI was low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 24 publications
6
55
3
Order By: Relevance
“…Excluding the 3% postmenopausal estrogen users from analysis did not alter the association of weight gain with postmenopausal breast cancer. In our study, we also found that weight gain is the main player in the inverse association of BMI at age 20 with postmenopausal breast cancer, a finding similar to that of the Iowa Women's Health Study 38 but disagree with that of the Nurse's Health Study. 10 Our findings are biologically plausible since weight gain during adulthood is accounted for largely by an increase in fat tissue, and excess body fat has been found to increase extra-ovarian production of estrogen and decrease sex hormone-binding globulin among postmenopausal women.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Excluding the 3% postmenopausal estrogen users from analysis did not alter the association of weight gain with postmenopausal breast cancer. In our study, we also found that weight gain is the main player in the inverse association of BMI at age 20 with postmenopausal breast cancer, a finding similar to that of the Iowa Women's Health Study 38 but disagree with that of the Nurse's Health Study. 10 Our findings are biologically plausible since weight gain during adulthood is accounted for largely by an increase in fat tissue, and excess body fat has been found to increase extra-ovarian production of estrogen and decrease sex hormone-binding globulin among postmenopausal women.…”
Section: Discussioncontrasting
confidence: 63%
“…This finding is consistent with those observed in the United States and European countries. 5,10,35,[37][38][39] In the large Adjusted for age, education, family history of breast cancer, ever had fibroadenoma, age at menarche, age at first live birth, exercise and age at menopause for postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Women who were perimenopausal at recruitment were excluded in this analysis. 2 Stratified by center and age at second weight assessment. 3 Stratified by center and age at second weight assessment, adjusted for BMI at recruitment (cont), smoking status and intensity (cat), alcohol user (yes/no), alcohol consumption (cont), education (cat), physical activity (cat), age at menarche (cat), age at first full-term pregnancy (cat), use of oral contraceptives (cat), menopausal status (cat), HRT use (cat), energy intake (cont) and time between two weight assessments (cont).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of cohort [1][2][3][4][5][6][7][8][9][10][11] and case-control studies, [12][13][14][15][16][17] the World Cancer Research Fund states that longterm adult weight gain (i.e., recalled weight gain since age 20) increases the risk of postmenopausal breast cancer and grades this relation as "probable". 18 Most studies investigated the association between longterm weight gain and breast cancer risk without a focus on a particular period in life.…”
mentioning
confidence: 99%
“…Both overweight and body weight uctuations during adult life are related to chronic disease risk. 1 ± 3 In particular, high weight gain has been associated with an increased morbidity from breast cancer, 4,5 cardiovascular disease in middle 6 and later 7 adulthood, and diabetes. 1 Still, the evidence for the effects of low weight, as well as weight loss or gain is somewhat controversial, with respect to the optimal weight for longevity, and it remains unclear which periods of life might be most crucial concerning weight-related health outcomes in old age.…”
Section: Introductionmentioning
confidence: 99%